Analisis Pemikiran K.H. Ahmad Dahlan dan K.H. Hasyim Asy'ari Terhadap Reformasi Pendidikan Islam di Indonesia - Muhtadi Abdul Mun’im; Masyhari Yanto (LP2M Universitas Ibrahimy, 2025)
Islamic education in Indonesia has undergone significant reform, with prominent figures such as K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari playing a significant role in shaping its development. This study explores the contributions of these two influential scholars to the modernization of Islamic education in Indonesia. Ahmad Dahlan, the founder of Muhammadiyah, advocated the integration of religious and secular education, encouraging critical thinking, community engagement, and the establishment of modern educational institutions. His educational approach emphasized character building and the application of innovative teaching methods to create a dynamic learning environment. On the other hand, Hasyim Asy'ari, the founder of Nahdlatul Ulama (NU), focused on preserving traditional Islamic scholarship while incorporating modern subjects into the pesantren curriculum. He emphasized the importance of maintaining the traditions of Ahl al-Sunnah wal-Jama'ah and encouraged students to apply their knowledge to improve society. This study analyzes the similarities and differences between their educational philosophies, revealing their shared commitment to Islamic education and contrasting approaches to reform. The research findings show that Ahmad Dahlan and Hasyim Asy'ari's contributions in creating a diverse and dynamic Islamic education landscape that blends tradition with modernity while encouraging social responsibility and community development. The legacy of these two scholars continues to shape contemporary Islamic education in Indonesia, with their influence clearly visible in the curriculum, teaching methods, and social engagement of Islamic educational institutions.